The Effect of Using Educational Media Brochures, Interactive Videos, and Picture Guessing Games on Knowledge and Attitudes Regarding The Prevention of Kidney Failure - Vionisa Wulandari (Poltekkes Kemenkes Mataram, 2023)
Background: Chronic kidney failure is a disorder of kidney function resulting in a condition in which the body fails to maintain metabolism and fluid and electrolyte balance, resulting in uremia. In the Province of West Java, including the Karawang area, the prevalence of patients with chronic kidney failure increases with age. This research was done to know the effectiveness of providing education using brochures, interactive videos, and picture guessing games for class XI students of SMAN 1 Telukjambe.Research Methods: This research is quantitative research with a quasi-experimental design. The sample selection used a random sampling technique, with the research method being the group pre-post test. The sample is students of class XI IPS 3, XI IPS 4, and XI IPS 5. The population of this research sample is all students of class XI SMAN 1 Telukjambe Karawang. The data collected is information on the characteristics of the respondents, including age, gender, height, and weight, as well as knowledge and attitudes before and after the intervention. Data collection was carried out by filling out the pre-test and post-test questionnaires that had been given. The data were then analyzed using a statistical test application to determine the effect of providing various education on the knowledge and attitudes of the respondents. Research Result: Brochures and picture guessing games are less effective in influencing knowledge and attitudes (p>0.05). Meanwhile, interactive video media provided an effective influence on learning (p=0.01<0.05) and attitudes (p=0.007<0.05) regarding chronic kidney failure education.. Conclusion: Interactive video media is the most suitable and accepted media to increase knowledge and attitudes regarding preventing chronic kidney failure in SMAN 1 Telukjambe Karawang students.